The Relationship between Vocabulary Mastery and Reading Comprehension of English Education Students at UNUSA - Mita Dewi Mukarromah; Tiyas Saputri (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study examined the relationship between vocabulary mastery and reading comprehension among English Education students at Universitas Nahdlatul Ulama Surabaya (UNUSA). A quantitative correlational design was employed to determine whether students’ vocabulary knowledge was significantly associated with their ability to comprehend English texts. The population consisted of 40 students from the 2023 and 2024 cohorts. Using stratified random sampling and the Lemeshow formula, 28 students were selected as participants. Data were collected through a vocabulary mastery test and a reading comprehension test. The vocabulary test assessed word meanings, synonyms, antonyms, and contextual word use, while the reading test measured students’ ability to identify main ideas, supporting details, references, implied meanings, and vocabulary in context. The data were analyzed using descriptive statistics and Pearson Product Moment Correlation. The findings showed that the students obtained a mean vocabulary mastery score of 77, categorized as good, and a mean reading comprehension score of 74, categorized as moderate. The correlation analysis produced an r-value of 0.61 with a significance value of 0.000, indicating a strong, positive, and statistically significant relationship between the two variables. These findings suggest that students with broader vocabulary knowledge tend to comprehend English texts more effectively. Therefore, systematic vocabulary development should be integrated into reading instruction through contextual exercises, extensive reading, and independent learning activities.